Protestantism and public life: the Church of Ireland, disestablishment, and Home Rule, 1864-1874 - Golden, JJ (2011)
This thesis explores the hitherto undocumented disestablishment and reconstruction of the Anglican Church of Ireland, c.1868-1870, and argues that this experience was formative in the emergence of Home Rule. Structurally, the Church’s General Synod served as a model for an autonomous Irish parliament. Moreover, disestablishment and reconstruction conditioned the political trajectories of the Protestants initially involved in the first group to campaign for a federal Irish parliament, the Home Government Association (HGA). More broadly, both the HGA and the governance of the independent Church—the General Synod—grew from the bedrock of the same associational culture. The HGA was more aligned with the public associations of Protestant-dominated Dublin intellectual life and the lay associational culture of the Church. Although the political vision advocated was different from the normal conservatism of many of its Protestant members, culturally it was entirely grounded in the recent Anglican experience.